Application of the teaching games for understanding model to improve decision-making in sport learning: a systematic review and meta-analysis - Gabriel González-Valero; José Luis Ubago-Jiménez; Eduardo Melguizo-Ibáñez; Rubén Fernández-García (BMC Psychology)
Abstract Background Issues related to sport teaching at different educational stages is a subject of wide interest. Teaching Games for Understanding has been established as the most effective way to teach students the elements related to the field of sport. The objectives of this study were (a) to examine the impact of the Teaching Games for Understanding model on decision-making in sports education and (b) to compare the effect of the interventions analysed according to educational stage. Method A systematic review and meta-analysis of studies published before August 2024 was conducted. A total of 4937 scientific studies were obtained. The quantitative synthesis consisted of 25 scientific articles (n = 1692). The studies were analyzed using three-level random effects models with variance estimation. Results were calculated as raw mean differences and Hedges’ g effect sizes. Results This model is suitable for decision-making in sports education (g = 0.82; CI 95% = [0.55; 1.09]). This pedagogical model was also found to be effective for working on decision-making in primary education (g = 0.6108; CI 95% = [0.3587; 0.8628]), secondary education (g = 0.7523; CI 95% = [0.2348; 1.2706]) and higher education (g = 0.8803 [CI 95% = 0.2851 to 1.4855]). Conclusions Teaching games for understanding effectively addresses decision-making during sports learning. In addition, this pedagogical model is effective for facilitating decision-making according to the role and the moment of the game. The use of this model enables effective technical-tactical learning to solve various problematic actions in real game situations.